A quasi experimental study to assess the effectiveness of standard operating procedures on prevention and management of needle stick injury in a teaching hospital of Haryana, India - Kaushik, Annu; Jyoti, Sarin (International Journal of Research in Medical Sciences, 2017)
Background: Nurses spend most of the time with patients and provide the most direct patient care; nurses are also the healthcare workers that are most susceptible to worksite-related medical problems the most common one being needle stick injuries. Adequate training will empower the nurses to protect themselves and effectively manage needle stick injuries. The aim of the study was to assess the effectiveness of standard operating procedures (SOP) in prevention and management of needle stick injuries. Methods: A quasi experimental study was conducted among nurses working in two teaching hospitals in Haryana A total of 150 nurses were included in the study. The tools included a knowledge questionnaire and a SOP on prevention and management of needle stick injuries. Results: There was a significant increase in the post test knowledge score of the experimental group -27.74 (day 9) and 24.13 (day 40) as compared to the pre-test knowledge score (21.00). However, there was no significant increase in the post test score on day 70 (22.26). Conclusions: Training of nurses is vital in prevention of needle stick injuries however continuous reinforcement is required for the sustainability of knowledge.